Mathematical Modeling of Thermal and Deformation Fields in Non-Metallic Heterogeneous Materials During Control by the Thermal Imaging Method - Vladimir Tonkonogyi; Maryna Holofieieva; Yurii Morozov; Volodymyr Yarovyi; Oksana Bieliavska; Isak Karabegović (Журнал інженерних наук)
The article aims to mathematically model processes that occur in non-metallic heterogeneous materials when active thermography methods were used for deep study control. Currently, the trend in industrial development is using non-metallic heterogeneous mediums as a system of various components as structural materials. Such materials are characterized by improved physical and mechanical properties, which can be adjusted by selecting compositions and the ratio of component phases and macrostructure. At the same time, they are characterized by disadvantages such as variability of volume and time properties and the presence of various defects. Effective control methods are of particular importance to ensure the quality and reliability of products made from materials of this class. In the article, the authors analyzed the capabilities of existing non-destructive testing methods for flaw detection of products made of non-metallic heterogeneous materials. When developing a new and improving an existing measurement method, the problem of establishing a set of radiation parameters was used. This allowed for describing the state of the material with the necessary accuracy and the functional connections of these parameters with the latter’s characteristics.